2017
DOI: 10.1155/2017/3054145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Huayu Tongluo Herbs on Reduction of Proteinuria via Inhibition of Wnt/β‐Catenin Signaling Pathway in Diabetic Rats

Abstract: The study investigated the expression of Wnt/β-catenin pathway in diabetic rats and the intervention effect of Huayu Tongluo herbs (HTH). Ten rats were randomly selected as control group and the remaining rats were established as diabetic models. The diabetic rats were randomly divided into model group and HTH treatment group. The intervention was intragastric administration in all rats for 20 weeks. At the end of every 4 weeks, fasting blood glucose and 24 h urinary total protein quantitatively were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Accumulating experiment and clinical studies have demonstrated that many traditional Chinese medicines (TCM) or active ingredients of TCM had preventive and therapeutic effects on kidney damage caused by diabetes [12]. Blood stasis blocking the collaterals of kidney is one of the main pathogeneses in DN and has been widely approved by the academic circles of TCM [13]. Our previous research also confirmed that Huayu Tongluo herbs had protective effect on renal tissues of diabetic rats [13].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Accumulating experiment and clinical studies have demonstrated that many traditional Chinese medicines (TCM) or active ingredients of TCM had preventive and therapeutic effects on kidney damage caused by diabetes [12]. Blood stasis blocking the collaterals of kidney is one of the main pathogeneses in DN and has been widely approved by the academic circles of TCM [13]. Our previous research also confirmed that Huayu Tongluo herbs had protective effect on renal tissues of diabetic rats [13].…”
Section: Introductionsupporting
confidence: 57%
“…After one week of adaptive rearing with regular rodent chow (protein 21.1%, fat 4.5%, carbohydrate 60.6%; Botai Hongda Biotechnology Co., Ltd., Beijing, China, http://biotech-hd.cn.gongchang.com), all rats were randomly assigned into the control group (C group, n � 8) and diabetic group (n � 40) according to the random number table method. e rats in the C group were still bred with regular rodent chow, while the diabetic group rats were bred with high-fat diet (HFD, protein 24.2%, fat 25.4%, carbohydrate 42.1%; Botai Hongda Biotechnology Co., Ltd., Beijing, China, http://biotech-hd.cn.gongchang.com) for the initial period of 6 weeks according to the method designed by us previously [13]. After fasting overnight, the diabetic group rats were administered intraperitoneal injection of low-dose streptozotocin (STZ, Enzo Life Science Co., Ltd., USA, 35 mg/ kg) diluted with 0.1 M cold citrate buffer (pH 4.3).…”
Section: Animal Modeling and Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, An et al observed that hyperoside, a flavone glycoside with anti‐inflammatory, anti‐cancer and anti‐oxidan properties, prevents proteinuria in diabetic nephropathy . Furthermore, Bai et al found that Huayu Tongluo herbs inhibits the production of proteinuria in diabetic rats …”
Section: Discussionmentioning
confidence: 99%
“…The Notch pathway is downstream of the Wnt/β-catenin signal and thus determines the destiny of HF. In addition, in cell culture, where HFSCs differentiate into hair and the Lef1 gene is upregulated, the Wnt transcriptional target genes activate the target gene Jagged1 and directly activate Wnt/β-catenin and Notch signaling pathways ( Bai et al, 2017 ). In contrast, in stratified IFE, β-catenin is detected in proliferating basal cells, and Notch1 is primarily expressed in the differentiated basal layer.…”
Section: The Wnt/β-catenin Signaling Pathway and The Notch Signaling mentioning
confidence: 99%